(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Fertilization with essential mineral elements is important to get high quality yield results. The lack of necessary mineral elements in soil can affect oilseed rape plant physiological functions, photosynthesis and plant productivity. Oilseed rape plants have high requirements for nitrogen and as oil crop – for sulphur. The aim of the investigation was to explain changes of chlorophyll a fluorescence parameters in spring oilseed rape leaves and yield changes under nitrogen and sulphur supply. During laboratory experiments changes of chlorophyll a fluorescence parameters and during field experiments changes of yield parameters under different nitrogen and sulphur supply were observed. Laboratory and field experiments showed that sulphur fertilizer rate 18 kg ha-1 is the most effective sulphur dose for spring oilseed rape, when nitrogen 55 kg ha-1 is added, because its presence has positive effect on photosynthetic reactions. There was found out in laboratory experiments that chlorophyll a fluorescence parameters Fv/Fm and PI can be used to describe sulphur and nitrogen mineral element supply efficacy on spring oilseed rape. There was observed in the field experiment that oilseed rape yield increases significantly (from +0.34 t ha-1 to +0.64 t ha-1) under optimal (S18N55) nutrient supply, but lack of sulphur leads to significant yield losses. To avoid excessive fertilizer usage, its negative impact on plant physiology and yield losses, we consider that sulphur: nitrogen = 1:3 as additional fertilizer is optimal for spring oilseed rape plants.